Association between sarcopenia and kidney stones in United States adult population between 2011 and 2018 - Zhang, Yifan; Tian, Changxiu; Wang, Yidi; Zhang, Houliang; Ni, Jinliang; Song, Wei; Shi, Huajuan; Zhang, Tao; Xu, Changbao; Wang, Keyi; Peng, Bo (Frontiers in Nutrition, 2023)
Purpose: To investigate the relationship between kidney stones and sarcopenia in U.S. adult population between 2011 and 2018. Materials and methods: We conducted a cross-section study based on the National Health and Nutrition Examination Survey (NHANES)including 39156 individuals. Sarcopenia was assessed by the sarcopenia index. Association between kidney stones and sarcopenia verified by multiple logistic regression analysis and dose-response curves analysis using restricted cubic spline (RCS) regression. Meanwhile, propensity score matching (PSM) was performed to exclude the effect of confounding variables. Results: There were 9472 participants in the study by our accurate enrollment screening process. The odds of kidney stones decreased significantly with the increase of sarcopenia index. Logistic regreesion anlysis showed that sarcopenia expressed significant differences in the participants which suffered kidney stone before PSM (P <0.001). In model 4 adjusting all relevant covariates shown that adjusted odds ratio (aOR) of the 95% confidence intervals for kidney stones in all participants, age<39 years and age ≥40 years were respectively 1.286(1.006–1,643), 1.697(1.065–2.702) and 0.965 (0.700-1.330) for sarcopenia, and P values were 0.044, 0.026 and 0.827. After performing PSM, the aOR of the 95% in modal 4 for kidney stones in all participants and age<40 year were 2.365(1.598-3.500) and 6.793(2.619-17.6180) respectively(P<0.01), and especially the aOR in participants (age≥40) was 1.771(1.138-2.757) with P value being 0.011. Conclusion： Sarcopenia was positively related to the potential risk of kidney stones in the US adult population.